Identifying critical leadership styles of project managers for green building projects. Issue 2 (2nd April 2016) - Zhao, Xianbo; Hwang, Bon-Gang; Lee, Hong Ning
Abstract : In recent years, green building construction has been earning a significant place in Singapore's construction industry. The success of a green building project is inevitably associated with the leadership of the project manager. This study attempts to identify the leadership characteristics and styles of project managers in Singaporean green building projects. Conducting a questionnaire survey with 30 project managers experienced in green construction, this study identified 13 leadership characteristics, among which 'strive for work performance and productivity' was ranked top. Additionally, the 13 characteristics were categorized into two groupings: (1) directive and task-oriented leadership and (2) relationship-oriented leadership. The results indicated that the leadership style of the project managers was more towards directive and task-oriented leadership but did not overlook their relationships with subordinates. Therefore, this study provides an understanding of leadership characteristics and styles of project managers in green building projects for both practitioners and researchers.